The Academic Use of WhatsApp and Technostress: Investigating the Experience of Fatigue and Coping Behaviours among University Students - Al Abdullateef, Hafsa (2022)
The use of mobile instant messaging applications, such as WhatsApp, WeChat and Facebook messengers, has grown remarkably in recent years. WhatsApp is one of the most adopted mobile messaging apps, with two billion users worldwide. Due to its popularity among students, WhatsApp is being increasingly adopted for learning purposes in higher education. WhatsApp can provide students with various benefits that facilitate online learning and knowledge exchanges. However, despite these benefits, using WhatsApp can also have negative effects for students and their well-being. Research has demonstrated that the excessive use and heavy reliance on information and communication technology (ICT) can lead to technostress, a phenomenon that refers to the stress experienced by individuals due to the use of ICT. Thus, although WhatsApp offers students an effortless and fast means for communication and information sharing, the use of WhatsApp for academic and non-academic-related purposes can create fatigue for students. Research indicates that university students are vulnerable to different sources of stress including academic stressors. With the increased use of mobile technology for learning, students could face an additional source of academic stress caused by the educational use of technology. While there has been a growing interest in studying the educational benefits of using mobile instant messaging, there is still a lack of understanding around its negative effects on students and their academic performance. Addressing this issue becomes important given the consequences of technostress on individuals. The current study, therefore, aims to shed light on the negative aspects of the educational use of WhatsApp. Using the transactional model of stress and coping, the study seeks to explore factors that cause fatigue among university students when using WhatsApp for learning purposes and investigate students’ coping behaviours to reduce fatigue.